Electrospinning and thermal treatment of yttria doped zirconia fibres. Issue 10 (July 2017) - Castkova, Klara; Maca, Karel; Sekaninova, Jana; Nemcovsky, Jakub; Cihlar, Jaroslav
Abstract: As compared to a bulk material, the fibres exhibit novel physical and chemical properties arising from their unique geometric features such as high surface area, surface to volume ratio and small fibre diameter. This paper is focused on the fabrication of nanosized 8 mol% yttria doped zirconia fibres by electrospinning from propoxide/polyvinylpyrrolidonebased precursors and physical-chemical characterization of the ceramic fibres with an energy application potential. Fully crystalline composition of cubic zirconia was detected after fibre heat treatment at 700 °C. The fibre morphology was changed with increasing temperature from flexible nonsintered nanoparticle system at 700 °C through porous nanograin structure at 900 °C and nonporous structure with coarser nanograins at 1100 °C to fragile chain-like fibre structure formed of elongated submicrometer grains at 1300–1450 °C. The densification and grain growth kinetics were described in two stages in the temperature range from 700 °C up to 1450 °C.